Improving Students’ Learning Results Using The Study Group Method on Structure and Functions of Plants in Fourth Grade - Yulius Benny; Hilarius Jago Duda; Sirilus Sirhi (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2017)
The purpose of this study is to describe the cognitive achievement of students using the Study Group method on the material of structure and function of plant parts in fourth grade. This classroom action research (CAR) takes descriptive qualitative research method with qualitative approach. The subjects in this study were fourth graders of 21 people consisting of 8 male students and 13 female students. This study was conducted in two cycles. Each cycle consisted of planning, action, observation and reflection. The data collection tools were guidelines for observation, test questions, the questionnaire, and documentation. The research result showed that in the first cycle, the percentage of classical completeness was 61,90%. While on the second cycle, the significance increased to 90,48%. This was an increase in cognitive achievement of students from the first cycle to the second cycle of 28,58%.